EFEK MODERASI LINGKUNGAN KERJA PADA PENGARUH DISIPLIN KERJA DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT WIJA KUSUMA NADI DENPASAR BALI - Arifin, Miftahussurur; Soeliha, Siti; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Human resource management is an art or discipline that aims to manage and optimize the relationship and function of resources, especially individual labor, in an efficient and effective manner. With the aim of maximizing the function of resources so as to achieve the goals that the institution, agency, or company wants to achieve. The purpose of this study was to analyze the effect of work discipline and training variables on work productivity with work environment as a moderating variable at PT Wija Kusuma Nadi Denpasar Bali using structural Partial Least Square (PLS). The results of the direct effect hypothesis test using the SmartPLS 4.0 application, show that work discipline has a significant positive effect on work productivity, training has a negative and insignificant effect on work productivity, work environment strengthens the effect of discipline on work productivity, work environment weakens the effect of training on work productivity.